Melittin alleviates bleomycin-induced pulmonary fibrosis in vivo through regulating TGF-β1/Smad2/3 and AMPK/SIRT1/PGC-1α signaling pathways - Jiawang Yu; WeiHua Lu (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): The present study investigated the protective effect of melittin (MEL) against bleomycin (BLM)- induced pulmonary fibrosis (PF) in mice and the mechanism underlying this effect.Materials and Methods: A mouse model of PF was established by intratracheal injection of 3.5 mg/kg BLM. Twenty-four hours after the model was established, the mice in the treatment groups were intraperitoneally injected with MEL, and specimens were collected 28 days later. The body weight, survival rate, and pulmonary index (PI) of the mice were determined. Haematoxylin and eosin (HE) staining, Masson’s trichrome staining, immunohistochemical staining, kit assays, and Western blot (WB) analysis were performed.Results: Our study indicated that MEL significantly increased the body weight and survival rate, reduced PI, and improved lung histopathology in mice. In addition, MEL inhibited epithelial-mesenchymal transition (EMT) and extracellular matrix (ECM) deposition. Attenuated mitochondrial damage and reduced oxidative stress (OS) were also observed in MEL-treated mice. We further showed that MEL inhibited the TGF-β1/Smad2/3 pathway and activated the AMPK/SIRT1/PGC-1α pathway.Conclusion: MEL is a promising future therapeutic agent for PF. Its multifaceted and complex mechanism of action inhibits both EMT and ECM production by modulating the TGF-β1/Smad2/3 pathway. It also improves mitochondrial function and reduces OS at least partially through the activation of the AMPK/SIRT1/PGC-1α signaling pathway.